Synthesis of Pd3 Sn and PdCuSn nanorods with L12 phase for highly efficient electrocatalytic ethanol oxidation - Zhou, Ming (2022)
The crystal phase of nanomaterials is one of the key parameters determining their physicochemical properties and performance in various applications. However, it still remains a great challenge to synthesize nanomaterials with different crystal phases while maintaining the same composition, size, and morphology. Here, a facile, one-pot, wet-chemical method is reported to synthesize Pd3 Sn nanorods with comparable size and morphology but different crystal phases, that is, an ordered intermetallic and a disordered alloy with L12 and face-centered cubic (fcc) phases, respectively. The crystal phase of the as-synthesized Pd3 Sn nanorods is easily tuned by altering the types of tin precursors and solvents. Moreover, the approach can also be used to synthesize ternary PdCuSn nanorods with the L12 crystal phase. When used as electrocatalysts, the L12 Pd3 Sn nanorods exhibit superior electrocatalytic performance toward the ethanol oxidation reaction (EOR) compared to their fcc counterpart. Impressively, compared to the L12 Pd3 Sn nanorods, the ternary L12 PdCuSn nanorods exhibit more enhanced electrocatalytic performance toward the EOR, yielding a high mass current density up to 6.22 A mgPd -1 , which is superior to the commercial Pd/C catalyst and among the best reported Pd-based EOR electrocatalysts.